Mobiliser le paysage pour observer les territoires : quelles démarches, pour quelle participation des acteurs ? - Pierre Dérioz; Philippe Béringuier; Anne-Élisabeth Laques (Développement Durable et Territoires)
In the current context, which is characterized by a general need for territorial observation, landscape can be used both as an information source and as a support for public participation processes. Technical and political constraints are responsible for the different forms taken by the landscape observatories and for their limits. The paper first examines the approach of the landscape photographic observatories, generally only focused on the landscape for itself, with sometimes a real efficiency for the mobilisation of the local actors, but quite a poor valorisation of the landscape’s informative potential. Then two different experimentations using landscape as a tool for territorial observation and as a central information source are presented and analysed : the first one deals with the achievement of a territorial diagnosis in the Regional Nature Park of the Haut-Languedoc (2004-2008), as a preliminary step before the revision of its Chart. Still in its first stages, the second case study shows an attempt to combine a landscape-oriented approach and remote sensing data, and thus to produce spacialised informations about land-use, agrodiversity and biodiversity in western brazilian Amazonia (High-Solimoes).